Activation induced cell death (AICD) of human melanoma antigen-specific TCR engineered CD8 T cells involves JNK, Bim and p53. (1st February 2017) - Chhabra, Arvind; Mukherji, Bijay; Batra, Deepika
ABSTRACT: Objectives : Adoptive cancer immunotherapy (ACT) with transgenic T cell receptor (TCR) engineered (TCReng) anti-tumor T cells has produced encouraging results, however, efficacy of these approaches need improvement. Since premature activation induced cell death (AICD) of adoptively administered T cells could be a major impediment, we examined the mechanism(s) underlying AICD in TCReng CD8+ cytolytic T lymphocytes (CTL). Methods : AICD in human tumor antigen-specific MHC class I restricted TCR engineered CD8+ CTL was induced by exposing them to cognate peptide epitope. Results : We show that TCReng CD8+ human primary CTL undergo AICD even upon encountering their cognate peptide epitope for the very first time. AICD in TCReng CTL is a death-receptor-independent, JNK activation-driven intrinsic processes, in which p53-mediated mitochondria-centric, non-transcription-dependent pathway plays an essential role. Activated JNK modulates mitochondrial membrane integrity in CTL undergoing AICD by directly interacting with Bcl family protein, Bim, and the mitochondrial membrane pore complex, voltage dependent anion channel (VDAC), leading to the release of caspase-independent death executioner, apoptosis inducing factor (AIF), accumulation of single strand DNA breaks and eventually to cell death. Conclusions : Our findings offer opportunities to interfere with AICD in TCReng CD8+ anti-tumor CTL for sustaining them longer for producing better clinical outcomes.